2020
DOI: 10.1111/ppl.13183
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomewide isolation and expression of NF‐Y gene family in male cone development and hormonal treatment of Pinus tabuliformis

Abstract: It is known that nuclear factor Y (NF-Y) transcription factors play an important role in flowering time regulation and hormone response (ABA, GA) in angiosperms, but, little known in conifers. Moreover, the NF-Y gene family has not been comprehensively reported in conifers. Here, we identified 9 NF-YA, 9 NF-YB and 10 NF-YC genes in Pinus tabuliformis using Arabidopsis NF-Y protein sequences as queries. Additionally, by comparing conserved regions and phylogenetic relationships of the PtNF-Ys, we found that NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…WRKY75 could also positively regulate the JA-mediated plant defense against B. cinerea and A. brassicicola by regulating genes such as ORA59 and PDF1.2 in Arabidopsis (Chen et al, 2020). In Pinus tabuliformis, the NF-Ys were shown to respond to SA and JA treatments, which suggests their roles in affecting disease resistance by dynamically regulating SA and JA signaling (Guo et al, 2020). In this study, the PdbNF-Y promoters contain elements related to hormone response (Figure 4), and the protein-protein interaction (PPI) network showed that the PdbNF-Ys may interact with TFs involved in plant hormone signal transduction, such as ERF, MYB, WRKY, and bHLH (Figure 5, Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WRKY75 could also positively regulate the JA-mediated plant defense against B. cinerea and A. brassicicola by regulating genes such as ORA59 and PDF1.2 in Arabidopsis (Chen et al, 2020). In Pinus tabuliformis, the NF-Ys were shown to respond to SA and JA treatments, which suggests their roles in affecting disease resistance by dynamically regulating SA and JA signaling (Guo et al, 2020). In this study, the PdbNF-Y promoters contain elements related to hormone response (Figure 4), and the protein-protein interaction (PPI) network showed that the PdbNF-Ys may interact with TFs involved in plant hormone signal transduction, such as ERF, MYB, WRKY, and bHLH (Figure 5, Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor (TF) that regulates plant growth and stress resistance, the NF-Y has been identified and studied in multiple plants. There were 36 NF-Ys in A. thaliana (Siefers et al, 2009), 25 NF-Ys in Ricinus communi (Wang et al, 2018), 59 NF-Ys in Solanum lycopersicum , 32 NF-Ys in Vitis vinifera (Ren et al, 2016), 33 NF-Ys in Juglans regia (Quan et al, 2018), 24 NF-Ys in peach (Li et al, 2019), 28 NF-Ys in Pinus tabuliformis (Guo et al, 2020), 52 NF-Ys in P. trichocarpa (Liu et al, 2021), and 46 NF-Ys in P. tomentosa (Li et al, 2022). In this study, a total of 26 NF-Y members were cloned in P. davidiana × P. bollena, including 12 PdbNF-YAs, six PdbNF-YBs, and eight PdbNF-YCs (Table 1, Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…NF‐YB and NF‐YC can form a heterodimer, which then binds to the binding domain on NF‐YA to form heterotrimers (Nardone et al ., 2017). The heterotrimeric transcription factor NF‐Y has been reported to play an important role in plant growth and development and stress response (Mu et al ., 2013; Lian et al ., 2018; Das et al ., 2019; Guo et al ., 2021). As the most important component factor of heterotrimers, the NF‐YA subunit contains two structurally extended α‐helices; one is involved in the NF‐YB/NF‐YC binding domain, and the other is positioned deep into the DNA minor groove, providing exquisite sequence specificity for recognition and binding of the CCAAT box (Nardone et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, each NF-Y subfamily in plants consists of multiple members. At present, NF-Y family members have been identified in many species, including Arabidopsis [ 12 ], rice [ 13 ], maize [ 14 ], tomato [ 15 ], poplar [ 16 ], and Pinus tabuliformis [ 17 ]. Some species members expanded, resulting in functional redundancy and functional differences, while also helping to form a transcription factor network to regulate plant growth and development [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%